IMPLIKATUR PERCAKAPAN DALAM DIALOG INTERAKTIF HOTMAN PARIS SHOW INEWS (CONVERSATIONAL IMPLICATURES IN THE INTERACTIVE DIALOGUE OF HOTMAN PARIS SHOW INEWS) - Siti Nia Audina (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2022)
AbstractConversational implicatures in the interactive dialogue of Hotman Paris show inews.This study has three objectives. First, how the implicature of the conversation in theHotman Paris Show interactive dialogue will take shape. Second, what is the implicatureof the conversation in the Hotman Paris Show interactive dialogue. Third, what is theconventional implicature of the conversation in the Hotman Paris Show interactivedialogue. The basic theory used by researchers is the theory of speech acts from Searle,namely representative, commissive, directive, and expressive speech acts. The four speechacts as a reference for analyzing the form of conversational implicature, the purpose ofconversational implicature, and conventional implicature. This research is a qualitativedescriptive study. The data source of this research is the interactive dialogue video of theHorman Paris Show INEWS with sources from episodes in July-August 2019, while thedata in this study are speeches that are suspected of containing conversational implicaturein Hotman Paris Show INEWS interactive dialogue with sources from episodes in themonth July-August 2019. The data collection of this study used the method of note takingwith note technique. The instrument in this study was the researcher himself in the form ofa primary data collection tool. Data analysis is carried out in stages: (1) identifyingfindings data, (2) classifying or grouping research data based on conversationalimplicature, conversational implicative intent, and conventional implication, (3)interpreting or interpreting data based on conversational implicature, conversationalimplicature, and conventional implicators that have been classified, (4) describe theresults of data analysis. In accordance with the formulation of the problem above, theresults of this study are (1) the study found four forms of conversational implicature in theform of speech acts in the interactive dialogue Hotman Paris Show INEWS with speakersfrom episodes in July-August 2019, namely: 1) representative, 2) commissive, 3) directive,and 4) expressive. (2) the researcher found eight intentions of conversational implicaturein the form of speech acts, namely 1) stating, 2) explaining, 3) giving testimony, 4) urging,5) rejecting, 6) acknowledging, 7) insinuating, 8) telling. (3) the researchers found nineutterances of conventional implicature.Key words: pragmatic, implications, purpose, being, conventional implicationsAbstrakImplikatur percakapan dalam dialog interaktif hotman paris show inews. Penelitianini memiliki tiga tujuan. Pertama, bagaimana wujud implikatur pada percakapan dalamdialog interaktif Hotman Paris Show. Kedua, bagaimana maksud implikatur padapercakapan dalam dialog interaktif Hotman Paris Show. Ketiga, bagaimana implikaturkonvensional pada percakapan dalam dialog interaktif Hotman Paris Show. Teori dasaryang digunakan peneliti adalah teori tindak tutur d ari Searle, yakni tindak tuturrepresentatif, komisif, direktif, dan ekspresif. Keempat tindak tutur tersebut sebagai acuanuntuk menganalisis wujud implikatur percakapan, maksud implikatur percakapan, danimplikatur konvensional. Penelitian ini termasuk jenis penelitian deskriptif kualitatif.Sumber data penelitian ini adalah vidio dialog interaktif Hotman Paris Show INEWSdengan narasumber dari episode di bulan Juli-Agustus 2019, sedangkan data dalampenelitian ini berupa tutura-tuturan yang dicurigai mengandung implikatur percakapandalam dialog interaktif Hotman Paris Show INEWS dengan narasumber dari episode dibulan Juli-Agustus 2019. Pengumpulan data penelitian ini menggunakan metode simakdengan teknik catat. Instrumen dalam penelitian ini yaitu peneliti itu sendri yang berupaalat pengumpul data utama. Analisis data dilakukan dalam tahap: (1) mengidentifikasi datahasil temuan, (2) mengklasifikasi atau mengelompokkan data penelitian berdasarkan wujudimplikatur percakapan, maksud implikatur percakapan, dan implikatur konvensional, (3)menginterpretasikan atau menafsirkan data berdasarkan wujud implikatur percakapan,maksud implikatur percakapan, dan implikatur konvensional yang sudah diklasifikasikan,(4) mendeskripsikan hasil analisis data. Sesuai dengan rumusan masalah di atas, hasil daripenelitian ini adalah (1) penelitian menemukan empat wujud implikatur percakapan berupatindak tutur dalam dialog interaktif Hotman Paris Show INEWS dengan narasumber dariepisode di bulan Juli-Agustus 2019, yakni: 1) representatif, 2) komisif, 3) direktif, dan 4)ekspresif. (2) peneliti menemukan delapan maksud implikatur percakapan berupa tindaktutur, yakni: 1) menyatakan, 2) menjelaskan, 3) memberikan kesaksian, 4) mendesak, 5)menolak, 6) mengakui, 7) menyindir, 8) memberitahukan. (3) peneliti menemukansembilan tuturan implikatur konvensional.Kata-kata kunci: pragmatik, implikatur, maksud, wujud, implikatur konvensional